Portfolios of the poor : how the world's poor live on $2 a day - Collins, Daryl; Morduch, Jonathan; Rutherford, Stuart; Ruthven, Orlanda (Princeton University Press, 2009)
The authors report on the yearlong "financial diaries" of villagers and slum dwellers in Bangladesh, India, and South Africa--records that track penny by penny how specific households manage their money--From publisher description